Exergaming With Integrated Head Turn Tasks Improves Compensatory Saccade Pattern in Some Patients With Chronic Peripheral Unilateral Vestibular Hypofunction - Swanenburg, Jaap; Büchi, Fabienne; Straumann, Dominik; Weber, Konrad P.; de Bruin, Eling D. (Frontiers in Neurology, 2020)
This study aimed to determine whether vestibular rehabilitation using active video games (Exergames) may facilitate vestibular compensation and gait in patients with one-sided chronic peripheral vestibular hypofunction (cPVH). 12 patients with cPVH (mean age of 65 ± 12 years, 8 male) were recruited for a four-week baseline control followed by a four-week intervention period. The intervention included exergames requiring physical and cognitive tasks to play the game with 160 min of exergaming (eight sessions). The patients had to turn their heads constantly while playing the game. Dynamic visual acuity (DVA) with Vestibulo-Ocular reflex (VOR) gain deficit and cumulative overt saccade amplitude (COSA) were measured with the video head-impulse test. Additionally, functional gait assessment (FGA), Extended Timed Get-Up-and-Go (ETGUG), and Dizziness handicap inventory (DHI), were assessed. Results: DVA showed no significant group level change (p = 0.475, z = -0.714, d = 0.295) with a small effect size and improvements in five out of 12 patients. Ipsilesional VOR gain did not improve (p = 0.157, z = -1.414, d = 0.481) on group level while there was an intermediate effect size and improvements in six out of 12 patients. COSA got significant smaller (p = 0.006, z = -2.746, d = 1.354) with improvements in seven out of 12 patients. The contralesional sides did not change. The FGA for the group significantly improved with an intermediate effect size (p < 0.001, z = −3.08, d = 1.617) and five individuals showed clinically relevant improvements. The ETGUG group value improved significantly with a strong effect size (p < 0.001, z = -2.67, d = 1.030), with seven individuals contributing to this change. The DHI showed no change (p = 0.172, z = -1.381, d = 0.592) neither on the group nor on the individuals’ level. The game scores of the patients improved during the intervention period of the intervention for every game. Conclusion: The results of this study demonstrate that exergaming with promoted head turns facilitates vestibular compensation in patients with cPVH. This is the first study that shows an improvement in cumulative overt saccade amplitude after exergaming in chronic vestibular patients.